Translational Medicine Guide transforms drug development processes: the recent Merck experience - Hugues Dolgos; Mark Trusheim; Dietmar Groß; Joern-Peter Halle; Janet Ogden; B Osterwalder; Ewen Sedman; Luciano Rossetti (2016)
Merck is implementing a question-based Translational Medicine Guide (TxM Guide) beginning as early as lead optimization into its stage-gate drug development process. Initial experiences with the TxM Guide, which is embedded into an integrated development plan tailored to each development program, demonstrated opportunities to improve target understanding, dose setting (i.e., therapeutic index), and patient subpopulation selection with more robust and relevant early human-based evidence, and increased use of biomarkers and simulations. The TxM Guide is also helping improve organizational learning, costs, and governance. It has also shown the need for stronger external resources for validating biomarkers, demonstrating clinical utility, tracking natural disease history, and biobanking.